Investigating the Dielectric Strength Restoration Velocities of Multi-Break Vacuum Circuit-Breakers - Saafan, E. (New Approaches in Engineering Research Vol. 9, 2021)
Vacuum circuit-breakers with multi-break interrupters have become the most popular high-voltage circuit-breakers with high breaking capacity that are not environmentally hazardous. In this chapter the dielectric properties of multi-break interrupters of vacuum circuit-breakers were considered. The dielectric strength restoration velocities of multi-break vacuum interrupters were investigated.